Private investigator - Rolls, Alistair, 1971-; Franks, Rachel (Crime uncovered series., 2016)
"The private investigator is one of the most enduring characters within crime fiction and in Crime Uncovered: Private Investigator, editors Alistair Rolls and Rachel Franks dive deep into crime literature and culture in an attempt to unravel the mystery of this alluring and enigmatic figure. Assembling a cast of notable crime fiction experts, the book examines characters from the page and screen from Dashiell Hammett's Sam Spade -- the image of the hard-boiled loner trawling the mean streets -- to Agatha Christie's Captain Hastings -- the genteel companion in greener surrounds -- as well as other examples from international noir including Giorgio Scerbanenco's Duca Lamberti, Léo Malet's Nestor Burma, and many more. Including case studies, general essays, interviews with crime writers Leigh Redhead, Nick Quantrill, and Fernando Lalana, and analyses of the transatlantic exchanges that helped to develop public perception of a literary and filmic type, Private Investigator seeks to redefine what we think we know about this fascinating protagonist."--Page 4 of cover.